Age and P–T conditions of the Gridino‐type eclogite in the Belomorian Province, Russia. (4th August 2017) - Yu, H. L.; Zhang, L. F.; Wei, C. J.; Li, X. L.; Guo, J. H.
ABSTRACT: Although eclogites in the Belomorian Province have been regarded as Archean in age and among the oldest in the world, there are also multiple studies that have proposed a Paleoproterozoic age. Here, we present new data for the Gridino‐type eclogites, which occur as boudins and metamorphosed dykes within tonalite–trondhjemite–granodiorite gneisses. Zircon from these eclogites has core and rim structures. The cores display high Th/U ratios (0.18–0.45), negative Eu anomalies and strong enrichment in HREE, and have Neoarchean U–Pb ages of c . 2.70 Ga; they are interpreted to be magmatic in origin. Zircon cores have δ 18 O of 5.64–6.07‰ suggesting the possibility of crystallization from evolved mantle‐derived magmas. In contrast, the rims, which include the eclogite facies minerals omphacite and garnet, are characterized by low Th/U ratios (<0.035) and flat HREE patterns, and yield U–Pb ages of c . 1.90 Ga; they are interpreted to be metamorphic in origin. Zircon rims have elevated δ 18 O of 6.23–6.80‰, which was acquired during eclogite facies metamorphism. Based on petrography and phase equilibria modelling, we recognize a prograde epidote amphibolite facies mineral assemblage, the peak eclogite facies mineral assemblage and a retrograde high‐ P amphibolite facies mineral assemblage. The peak metamorphic conditions of 695–755°C at >18 kbar for the Gridino‐type eclogites suggest an apparent thermal gradient of <39–42°C/kbar for the Lapland–Kola collisional orogeny.